2010
DOI: 10.1002/jmr.1033
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐histone H1 IgGs from blood serum of systemic lupus erythematosus patients are capable of hydrolyzing histone H1 and myelin basic protein

Abstract: Novel hydrolytic activity of the anti-histone H1 antibodies (Ab) toward histone H1 and myelin basic protein (MBP) was shown. Blood serum of ten patients with clinically diagnosed systemic lupus erythematosus (SLE), and nine healthy donors (control) were screened for the anti-histone H1 antibody- and anti-MBP antibody-mediated specific proteolytic activity. IgGs were isolated by chromatography on Protein G-Sepharose, and four of ten SLE patients appeared to possess IgGs that were capable of cleaving both histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 55 publications
2
32
0
2
Order By: Relevance
“…Antibodies possessing similar proteolytic activity were found in blood serum of multiple myeloma and multiple sclerosis patients [15,16]. We have shown that these proteolytically active AB can be classified as anti-histone auto-AB [17]. We also hypothesized that such AB could be responsible for the development of health disorders in SLE patients.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Antibodies possessing similar proteolytic activity were found in blood serum of multiple myeloma and multiple sclerosis patients [15,16]. We have shown that these proteolytically active AB can be classified as anti-histone auto-AB [17]. We also hypothesized that such AB could be responsible for the development of health disorders in SLE patients.…”
Section: Introductionmentioning
confidence: 89%
“…Isolation of IgG from blood serum was performed, as described earlier [17]. 2 ml of blood serum were precipitated with ammonium sulfate (50% saturation).…”
Section: Antibody Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…У той самий час ці ж антитіла були неактивні щодо гідролізу решти протеїнових субстратів (лізоцим, ци-тохром с, макроглобулін, казеїн, овальбумін, БСА). Необхідно відмітити, що подібну суб-стратну специфічність було виявлено також у протабзимів, виділених із сироватки крові хворих на СЧВ [17,26,29] та із молока дея- еКСПеРиМеНТАЛьНІ РОБОТи ких клінічно здорових жінокпороділь [26]. На відміну від протабзимів сироватки крові хво-рих на СЧВ, афінно очищені IgGантитіла си-роватки крові імунізованих мишей мали високу протеолітичну активність щодо корових гістонів тимуса теляти.…”
Section: результати та обговоренняunclassified
“…Колонку промивали ТБС, pH 7,5. Фракцію білків зі спорідненістю до сорбен-ту елюювали 3M NaCl, діалізували впродовж 18 год проти ТБС і антигістонові IgG-антитіла додатково очищали хроматографією на колонці із протеїн G-сефарозою згідно з [16]. IgG елюювали 0,1 М гліцин-НСІ, рН 2,6 і нейтралізували 1,5 М трис-HCl, pH 8,8, після чого АТ діалізували проти 20 мМ трис-HCl, pH 7,5 протягом 18 год.…”
Section: матеріали та методи дослідженьunclassified